Epidendrum scandens: an unusual new orchid species endemic to the Cordillera de Talamanca in Costa Rica - Karremans, Adam P.; Rojas-Alvarado, Gustavo; Chinchilla, Isler F. (Phytotaxa, 2023)
We describe and illustrate a new species of Epidendrum from the montane forests on the Cordillera de Talamanca, in Costa Rica. Epidendrum scandens is unusually among the ‘Rugosum subgroup’ of ‘Ramosum group’ in the plants forming large mats, composed of elongate, scandent, climbing stems that are notoriously branching and flexuous, becoming liana-like. The 2–3-flowered inflorescence is extremely discrete in relation to the stem, it bears typical yellowish-green flowers partially hidden by large floral bracts. The triangular lip is unusual in the conspicuous apical thickening. A taxonomic description, illustration, distribution map and conservation status are provided for the new species.